(untitled) (Docentes 2.0 Journal, 2024)
In the educational field, characterized by its rapid evolution, technology has emerged as a decisive factor, with artificial intelligence (AI) establishing itself as a fundamental catalyst in the sector’s transformation. The essay explores how the classification of AI tools in education can optimize teaching and learning processes by adopting an inductive method and hermeneutic paradigm with a qualitative, interpretive approach and topical narrative design. That allowed a deep exploration when classifying and studying the tools, thus identifying their distinctive characteristics and particular applications in various educational contexts and the effectiveness of learning. It was shown that effective classification of AI tools could be a vehicle to promote educational equity, ensuring that students of all socioeconomic levels and abilities have access to high-quality educational resources. By better understanding how these tools are classified, those involved in the educational process can expand their strategies to incorporate technologies ethically and equitably into educational systems. In conclusion, the importance of the detailed classification of artificial intelligence tools in education is underlined, proposing that a systematic and well-founded approach to integrating AI can revolutionize teaching and learning methods, adjusting them to contemporary needs and challenges of the educational field.